2010
DOI: 10.1111/igc.0b013e3181bbe933
|View full text |Cite
|
Sign up to set email alerts
|

Expression of hCG and GnRHs and Their Receptors in Endometrial Carcinoma and Hyperplasia

Abstract: The interaction between the hCG and LH/hCGR in endometrial tissue might stimulate cell growth and promote neoangiogenesis, whereas GnRHs, by binding to their receptors, could be responsible for the antiproliferative effect and stimulation of apoptosis. The identification of differences in the expression profile of the analyzed genes could be relevant for better understanding of the development of endometrial carcinomas and could be useful in clinical diagnostics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…Recently, it was shown that elevated levels of β-hCG in serum, urine or tumor tissue correlates with poor prognosis, aggressiveness and resistance to therapy in a variety of nontrophoblastic tumors, such as bladder, colon, lung (5) and testicular cancer (6). Moreover, it is also ectopically expressed in numerous gynecological malignancies, such as endometrial carcinoma (7), ovarian cancer (8) and cervical carcinoma (9,10). …”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was shown that elevated levels of β-hCG in serum, urine or tumor tissue correlates with poor prognosis, aggressiveness and resistance to therapy in a variety of nontrophoblastic tumors, such as bladder, colon, lung (5) and testicular cancer (6). Moreover, it is also ectopically expressed in numerous gynecological malignancies, such as endometrial carcinoma (7), ovarian cancer (8) and cervical carcinoma (9,10). …”
Section: Introductionmentioning
confidence: 99%
“…These two genes were selected because a number of studies have demonstrated that their expression level is up-regulated in gynecological tumors [ 32 - 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…The associations between the expression of LHCGR, the addition of LH/hCG and cell invasiveness should be substantiated in primary endometrial tissue samples and in cell lines. The results of previous studies have suggested that LHCGR + patients may benefit from a therapeutic strategy involving gonadotropin-releasing hormone (GnRH) analogues, since they were demonstrated to reduce the levels of LH (20,21). Furthermore, it has been reported that hCG regulates the expression of VEGF (22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%